Ultrafast Control of Interfacial Exchange Coupling in Ferromagnetic Bilayer. (2nd February 2023) - Liu, Xiao; Yuan, Haochen; Liu, Peiwen; Shi, Jingyu; Wang, Hailong; Nie, Shuaihua; Jin, Feng; Zheng, Zhe; Yu, Xuezhe; Zhao, Jianhua; Zhao, Haibin; Lüpke, Gunter
Abstract: Fast spin manipulation in magnetic heterostructures, where magnetic interactions between different materials often define the functionality of devices, is a key issue in the development of ultrafast spintronics. Although recently developed optical approaches such as ultrafast spin‐transfer and spin–orbit torques open new pathways to fast spin manipulation, these processes do not fully utilize the unique possibilities offered by interfacial magnetic coupling effects in ferromagnetic multilayer systems. Here, ultrafast optically controlled interfacial exchange interactions in the ferromagnetic Co2 FeAl/(Ga, Mn)As system at low laser fluence levels are experimentally demonstrated. The excitation efficiency of Co2 FeAl with the (Ga, Mn)As layer is 30–40 times higher than the case with the GaAs layer at 5 K due to the modification of exchange coupling interaction via photoexcited charge transfer between the two ferromagnetic layers. In addition, the coherent spin precessions persist to room temperature, excluding the drive of pump‐modulated magnetization in the (Ga, Mn)As layer and indicating a proximity‐effect‐related optical excitation mechanism. The results highlight the importance of interfacial exchange interactions in ferromagnetic heterostructures and how these magnetic coupling effects can be utilized for ultrafast, low‐power spin manipulation. Abstract : Ultrafast optically controlled interfacial exchange interactions in Co2 FeAl/(Ga, Mn)As heterostructures are demonstrated. The excitation efficiency of the bilayer is improved by 30–40 times as compared with single Co2 FeAl film at 5 K due to the modification of exchange coupling via photoexcited charge transfer between two ferromagnetic layers.